Description of Breast Care on Milk Production in Post-Partum Mothers in the Independent Practice of the Midwife Helen Tarigan and the Sahtama Clinic, Medan District Profits of 2021 - Jujuren Sitepu; Arihta Sembiring; Betty Mangkuji (PT FORMOSA CENDEKIA GLOBAL, 2023)
Unsmooth milk production is one of the factors causing failure in exclusive breastfeeding. Performing breast care can increase milk production in post-partum mothers. The purpose of this study was to determine the description of breast care in post-partum mothers on the frequency of breastfeeding babies on days 3 to 16 post-partum. This type of research uses the Analytical Descriptive method which serves to provide an overview of an object under study through data or samples collected without conducting analysis and making conclusions that apply to the public. The sample in this study were 12 mothers who breastfed their babies by doing breast care. Data analysis used in this research is univariate analysis. The results showed that 10 respondents had good milk production and 2 respondents had bad milk production after breast care. Poor milk production is caused by the mother's lack of knowledge and experience about breast care and how to breastfeed the baby properly. The conclusion from this study is that breast care is effective in increasing milk production because it is able to stimulate the milk glands in the breast so that milk production is more abundant and smooth by keeping the breasts clean and well cared for (nipples) because when breastfeeding the mother's breasts direct contact with the baby's mouth. It is hoped that the family will add more insight and knowledge about the benefits of breast care for milk production in post-partum mothers.